Power and Civil War Termination Bargaining1. Issue 1 (27th December 2014) - Park, Sunhee
<x xml:space="preserve">Abstract</x> Traditional bargaining theory predicts that groups will demand and concede as much as their relative power allows. However, scholars who study bargaining in the civil war context suggest that governments often overcompensate a rebel group to reach an agreement because the rebel group typically feels insecure. This paper argues that depending on the relative power distribution between groups, either a rebel group or government involved in a civil war can feel insecure at the bargaining table. The weaker bargaining participant, whether government or rebel, is expected to feel insecure and thus demand more political power in a postwar state than its power share predicts, while the stronger group is expected to be willing to overcompensate the weaker group to assuage its security concerns. Using a new data set on political power‐sharing bargaining during civil war, my analysis supports this expectation.